USING HISTORIC SITES IN DETERMINING PLANT-SOIL INTERACTIONS UNDER LONG TERM CONTAMINATED SOILS - LATEEF, E .M.ABD EL; HALL, J.E.; YASSEN, A.A.; EL-SALAM, M.S. ABD; SALEM, A.K.M. (Innovare Journal of Agricultural Sciences, 2021)
The relationships between heavy metals in soils and crop tissues are critical in understanding the potential risk to crop yields from Zn, Cu and Ni (the principal phytotoxic elements of concern in sludge), and the possible effects on dietary Cd (the critical zootoxic element that is labile in sludge-treated soil and readily absorbed by plants. These relationships cannot be derived from the agronomic trials because the quantities of heavy metals applied to the soil in sludge are small. These are field sites have been treated with sludge for many years in operational practice and where the oncentrations of heavy metals have been significantly raised above background values, representing potentially a worse-case of soil contamination. The purpose of the study was to provide a surrogate for long-term sludge-treated agricultural soil by examining the effects on crops of heavy metals in soil irrigated with raw sewage effluent for periods of more than 80 years and containing significantly elevated concentrations of heavy metals. Methodology: Two surveys of the Gabal El Asfar Old Farm were undertaken to assess the long-term effects of heavy metals in sludge-treated soil on crop quality. In the first survey, the relationships between total and DTPA extractable heavy metals in soil and concentrations in citrus fruit were examined. Concentrations of heavy metals in leaves of citrus were measured in the second survey and related to total and DTPA extractable metals in soil. The heavy metal contents of citrus leaves and fruit (orange - eleven sampling sites; mandarin - four sampling sites), and total and DTPA extractable concentrations in soils were measured in samples collected from different areas of the Farm during two site surveys. Total and DTPA concentrations of heavy metals in the surveyed soils showed significant enrichment by long-term irrigation with sewage effluent. For example, the maximum total concentrations of Zn and Cu were 530 and 366 mg kg-1, respectively, representing a potential risk to crop yields The maximum Cd concentration detected was 9 mg kg-1 and may be a potential risk to the human food chain from uptake into staple crops grown at the farm. DTPA extractable metals were significantly (P<0.001) correlated with the total contents of Zn (r=0.91***), Cu (r=0.83***), Ni (r=0.63***) and Pb (r=0.85***) in soil when data from both surveys were pooled for statistical evaluation. There was also evidence of a weak relationship between DTPA extractable Cd and the total soil Cadmium is the only element of concern in terms of the risk to human health from uptake into food crops grown on sludge-treated soil. The total Cd concentration in soil was raised to a value 3 times the maximum EU limit for this element in sludge-treated agricultural soil. Despite the marked increase in soil Cd content, there was no detectable transfer into citrus leaves or fruit (Figure 1). The absence of Cd uptake into citrus fruit is to be expected because fruits are amongst the least sensitive plant parts to Cd accumulation. These data emphasise the minimal risk to the human diet from Cd in fruit crops grown on sludge-treated soil. . In all cases, leaf tissue concentrations were low and in some cases Cu status was below the deficiency threshold. The Cd content in leaves was small and generally <0.02 mg kg-1 DM.